The impact of organizational culture on the creative behavior: case study in Sudanese bankers, 2021 - Mudawi, Sara Suliman Awawad; Mohammed, Elsheikh Mohammed Elkhidir; Al-Naeem, El-Fadil Suleiman El-Fadil (Journal of Economic, Administrative and Legal Sciences, 2022)
The study aimed to identify the impact of organizational culture in its dimensions on the dimensions of creative. The study used of the descriptive and analytical method and case study. The study population represented of Sudanese bankers and used the facilitated probability sample method; the study used a questionnaire to collect the data. (200) questionnaires were distributed and (178) valid for analysis were retrieved, a rate of (86%). the study use (AMOS) to analyze the data, and several statistical methods were used. In exploratory factor analysis, confirmatory factor analysis, Cranach's alpha coefficient, means and standard deviations, Pearson correlation analysis, structural equation modeling and path and regression analysis. The study showed that there is negative and significant relationship between organizational culture and creative behavior. The study recommended to applying study in other environments with different technical and organizational dimensions.
Keywords: organizational culture; organizational culture (values, attitudes, and norms); creative behavior (flexibility, originality)